A.I. and Law: Scope and Possible Challenges in Nepal - Silwal , Puja (Kathmandu School of Law Review, 2022)
This paper attempts to explore the interlink between law and artificial intelligence, focusing on its scope and challenges. Artificial Intelligence has galloped since its establishment, aiming to replicate the human mind into the machine. The biggest neighboring country has moved a step forward by developing the first lawyer robot, but in Nepal, its scope has yet to be researched and talked about. Thus, this paper looks into the rising scope and challenges of Artificial Intelligence in the legal sector in Nepal. It analyzes the scope of A.I. in the legal field to find out its importance in areas of law like legal research, case law management, e-discovery, document preparation, contract review, evidence evaluation, and many more. Despite having ample scope in the legal field, it faces numerous challenges, including the problem of costly implementation. There is a need for more knowledge among policymakers about AI-based tools to develop the nation. This paper concludes that implementing A.I. and law-based tools in Nepal is difficult despite having ample scope. Proper research should be carried out to implement the AI-based tool to replace the old traditional mechanism in the Legal field.